A Cross-Sectional Study of Depression, Insomnia, and Quality of Life Level among Community-Dwelling Older Adults - Bahtiar, Bahtiar; Nopriyanto, Dwi; Muda, Iskandar; Fitriani, Nurlaila; Hasan, Muhammad Kamil Che (Jurnal Berita Ilmu Keperawatan, 2025)
Older adults with depression and insomnia had increased, which affected their quality of life. This study investigates the correlation between depression and insomnia in older adults and their quality of life (QoL). This study used a quantitative descriptive method with a cross-sectional approach among 215 older adults in Indonesia, utilizing the Geriatric Depression Scale Short Form, insomnia rating scale, and WHO-QoL Bref for QoL assessment. The study was using the Spearman Correlation Test and multiple linear regression. The results show that depression is unrelated to physical, psychological, social, or ecological QoL. Insomnia was related to QoL of physical health (r = 0.138, p = 0.04) and QoL of psychological health (r = 0.140, p = 0.03), but insomnia was not associated with QoL of social health (r = 0.120, p = 0.06) or environmental health (r = 0.05, p = 0.38). Furthermore, the regression hierarchy analysis found that insomnia was the most dominant variable affecting the QoL on physical health (β = 0.17). There is a notable correlation between rates of insomnia and physical and psychological QoL that has essential implications for the health status and well-being of older adults. This finding suggests that nursing intervention may be necessary to address sleep disorders among older persons.